166k views
3 votes
If f(x) = 2x - 6 and g(x) = 3x + 9, find (f + g)(x).

2 Answers

1 vote

Answer:

(f-g)(x)= -x-15

Explanation:

just did it on apex test

User Lars D
by
4.8k points
3 votes

Answer:


\large\boxed{(f+g)(x)=5x+3}

Explanation:


(f+g)(x)=f(x)+g(x)\\\\f(x)=2x-6,\ g(x)=3x+9\\\\\text{Substitute:}\\\\(f+g)(x)=(2x-6)+(3x+9)\\\\=2x-6+3x+9\qquad\text{combine like terms}\\\\=(2x+3x)+(-6+9)\\\\=5x+3

User Guy Royse
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.